Thematic Organization of Conversations in the Voip Application Viber - Andreana Eftimova (Проблеми на постмодерността, 2020)
In a large number of social media and mobile applications, a new hybrid oral-writing formation is emerging, which is called from linguists' written spoken speech with similar features to both written and oral speech, but also has its own distinctive features. This study will illustrate the thematic structure of a conversation using the VoIP application Viber to highlight the most common model of a zig-zag themed organization and its specifics.